AVALIAÇÃO DA PERCEPÇÃO DA QUALIDADE DO AMBIENTE INTERNO POR TRABALHADORES DE ESCRITÓRIOS DURANTE A PANDEMIA - Ghidetti, Bianca Valadares (2021)
The COVID-19 pandemic forced office workers to carry out their work activities remotely from their homes for an extended period of time. Faced with this unexpected situation, emerged the need to know the characteristics of this new work environment and discover the level of users satisfaction with factors related to the quality of the internal environment. In order to do that, the research aimed to recognize the intensity of the main factors influence for the institutional environment and the residential work environment, in the context before the pandemic and current to the pandemic, according to the workers perception. The research methodology was divided into three stages: (1) definition of the object of study, selection and analysis of the building; (2) perception survey through the application of questionnaires; and (3) data analysis and elaboration of results. In the acoustic comfort, the noise sources that stood out in both environments for interfering with the ability to concentrate were: conversation and human activity. The thermal environment of JFES was perceived by most respondents as slightly cold and the residential environment predominantly ranged from neutral to very hot. In the air quality parameter, most respondents reported not feeling uncomfortable in both environments. The parameter of visual comfort showed high votes of satisfaction for the items view, natural light and general lighting for both environments. The last parameter analyzed was the layout and the satisfaction levels that presented the best evaluation were: finishes for two environments, interaction and furniture for JFES and visual privacy for the home office. In the result of the average ranking, the two environments had high ratings, with the average general perception higher for the residential environment. In the institutional environment, the variable that presented the most significant correlation with general satisfaction was: natural light. In the residential environment it was: individual space. No significant statistically correlation was found between the satisfaction and the individuals age group, but it was established between gender and satisfaction with the view/landscape and between occupation of the environment and sound privacy in the residential environment.